Sensorimotor skills in autism spectrum disorder: A meta-analysis. (August 2020) - Coll, Sarah-Maude; Foster, Nicholas E.V.; Meilleur, Alexa; Brambati, Simona M.; Hyde, Krista L.
Highlights: The present research provides a meta-analysis of studies on sensorimotor skills in ASD between 1980 and 2018. The findings confirmed that sensorimotor skills are strongly and consistently impaired in ASD across a broad range of skills ( g  = 1.22, p  < 0.001). The results also support a progressive increase in sensorimotor performance with age in ASD ( r  = 0.38; p  < 0.001). However, the results do not confirm an association between sensorimotor skills and clinical symptom severity ( r  = −0.19; p  = 0.12). Abstract: Background: Sensorimotor skills are often reported as atypical in individuals with autism spectrum disorder (ASD). Little is known about how sensorimotor skills in ASD may vary across development and with symptom severity. The main objective of this study was to conduct a comprehensive quantitative meta-analysis of sensorimotor skills in ASD. The specific aims were: to assess impairment of gross and fine sensorimotor skills in ASD, to examine the effect of age on sensorimotor skills in ASD and to examine the relationship between sensorimotor skills and ASD symptom severity. Method: An exhaustive search was conducted in Psycnet, PubMed, Web of Science and Cochrane Database to identify studies in ASD from 1980 to 2018 that involved quantitative evaluations of motor coordination, motor impairments, arm movement, gait, postural stability, visuomotor or auditory motor integration. A total of 139 studies were included and this represent 3436 individuals with ASD. Results: Results strongly support the presence of deficits in overall sensorimotor abilities in ASD (Hedges' g  = 1.22, p  <  0.001) and these atypicalities extended to fine and gross sensorimotor abilities. Sensorimotor abilities increased with age, but did not appear to covary with symptom severity. Conclusions: These results highlight the importance to target these deficits in future interventions and consider the impact of sensorimotor impairments across research, therapy, and educational settings.